2018
DOI: 10.4293/jsls.2018.00011
|View full text |Cite
|
Sign up to set email alerts
|

Self-Expanding Biodegradable Stents for Postoperative Upper Gastrointestinal Issues

Abstract: Background and Objectives:Endoscopic stenting is a minimally invasive treatment modality for patients with various gastrointestinal conditions. We evaluated the safety and efficacy of uncovered biodegradable stents for postoperative leaks and strictures in the upper gastrointestinal tract.Methods:This was a retrospective study of patients treated endoscopically with biodegradable stents from January 2010 through November 2017.Results:Thirteen patients were enrolled, 7 of whom were men. Their mean age was 46 (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Regarding role of BDS in management of esophageal transmural defects (Figures 1(c) and 1(d) ), the data is limited, with only two studies, comprising of 13 and 4 patients, wherein the clinical success ranged from 77.8 to 100%, but a drawback of mucosal reaction (2/4 patients) causing dysphagia requiring endoscopic dilation [ 25 , 26 ].…”
Section: Biodegradable Stentsmentioning
confidence: 99%
“…Regarding role of BDS in management of esophageal transmural defects (Figures 1(c) and 1(d) ), the data is limited, with only two studies, comprising of 13 and 4 patients, wherein the clinical success ranged from 77.8 to 100%, but a drawback of mucosal reaction (2/4 patients) causing dysphagia requiring endoscopic dilation [ 25 , 26 ].…”
Section: Biodegradable Stentsmentioning
confidence: 99%
“…20 Side effects of stent placement include chest pain, foreign body sensation, stent migration, and mucosal erosion, though serious adverse events occur in less than 5% to 10% of procedures. 20,21 Endoscopic suturing alone as well as the use of over the scope clips (OTSC; Ovesco Endoscopy Gmbh, Tubingen, Germany) have also demonstrated efficacy in the closure of esophageal defects and can be used for management of anastomotic leaks in the right setting with experienced providers. Success rates for endoscopic clipping vary widely and are limited by somewhat smaller sample sizes but range from 56% to 100%.…”
Section: Anastomotic Leaksmentioning
confidence: 99%
“…Biodegradable stents made of woven polydioxanone monofilament (SX-Ella; Milady Horakrove, Hradc Kralove, Czech Republic), which degrade by random hydrolysis accelerated by a low ambient pH have also been used in the management of upper gastrointestinal (GI) anastomotic leaks (23). Multiple studies have reported successful use of these biodegradable stents in closure of anastomotic leak after esophagectomy, diverticulectomy, gastric sleeve and gastrectomy in 80-85% of patients studied (23,24). Although biodegradable stents eliminate complications involved in stent removal and reportedly have a lower migration rate, they are more expensive (24).…”
Section: Endoluminal Stentmentioning
confidence: 99%
“…Multiple studies have reported successful use of these biodegradable stents in closure of anastomotic leak after esophagectomy, diverticulectomy, gastric sleeve and gastrectomy in 80-85% of patients studied (23,24). Although biodegradable stents eliminate complications involved in stent removal and reportedly have a lower migration rate, they are more expensive (24). Additionally, many patients in this study exhibited concerning side effects including drooling, retrosternal pain, sensation of having a foreign object in the body, and aversion to water for up to 2 months (24).…”
Section: Endoluminal Stentmentioning
confidence: 99%
See 1 more Smart Citation